URAPIDIL IN THE TREATMENT OF MEDICAL EMERGENCIES CAUSED BY BLOOD PRESSURE INCREASE - N. I. Gaponova; V. R. Abdrakhmanov; S. N. Tereschenko (Рациональная фармакотерапия в кардиологии, 2015)
Results of experimental and clinical studies devoted to urapidil combining central antihypertensive effect with peripheral vasodilatation are discussed. Scope of urapidil application is described; its good tolerability and safety are highlighted. Urapidil mode of application in different clinical situations accompanying by acute increase in blood pressure is specified.